In vitro release of enzymes and surfaces morphology of enzyme coated pelleted goat feed - Misbah, Maznah (2016)
In the current study, effectiveness of mixed enzymes, β-mannanase (Hemicell L-W) and phytase (Finase L) coating on goat pelleted feed was investigated using a simulated rumen. Feed incorporated with enzymes coating is believed to be a beneficial method for the delivery of enzymes to targeted digestive areas. The coating effects were analyzed to understand the correlation of coating efficiency, profile of enzyme release and physical appearance. The coating process was conducted using a spray process. Freshly formulated basal ingredients consisted of palm kernel and wheat-based diet, were prepared using pelletizing method. After cooling, initial pellet and coated pellet were analyzed to determine the surface morphology and coating efficiency. The coated pellet from scanning electron microscope (SEM) showed a homogenous and smooth surface without any pores or cracks on its morphology. Micrographs from SEM showed that the coating was successfully segregated during spraying process. Cross-sectional morphology showed a thin plate-like characteristic with lots of twisting and turning routes that allow liquid to enter easily. The coated pellet surfaces showed a darker colour of brown (hue of red and green 4.10 ± 0.30, yellow and blue 14.70 ± 0.30, lightness 37.57 ± 0.51) compared with initial pellet (red and green 5.00 ± 0.35, yellow and blue 15.97 ± 0.25, lightness 39.43 ± 0.29) which demonstrates a significant difference (P<0.05) through colour measurement analysis. The difference was attributed to the original dark brown of mixed enzymes colour. In this study, the different absorbance values obtained between initial pellet and coated pellet indicated a high coating efficiency of 75 %. It indicated a high degree of protection in vitro in rumen. The thickness of coating detected had been infused at range of 195 to 269 ± 52 μm. The mixed enzyme showed a successful delayed on its release profile in simulated rumen fluid (pH of 6.8), whereby the release profile showed a constant discharged at an average of 8 % on coated pellet compared to the uncoated pellet. The highest peak of enzyme release was observed at 96.7 % after six hour. The high release profiles at 0 to 30 minutes on both uncoated and coated pellet at 16.6 % and 45.8 % were contributed from activation of enzymes on feed ingredients. The coated feed has improved the resistance time until it was transferred to the next phase of gut, abomasum. Results of surface morphology and coating efficiency provided valuable information for incorporation of enzymes coating into goat feed.